Peningkatan Kesejahteraan Masyarakat Melalui Program “Berkah Produktif Dari Sampah” Di Desa Titik Kecamatan Semen Kabupaten Kediri - Meilina, Restin; Aliami, Sri; Ichsannudin; Silalahi, Amat Pintu Batu; Leksono, Poniran Yudho; Widodo, Moch. Wahyu; Muslih, Basthoumi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
This activity aims to improve the welfare of the society through the “productive blessings from waste” program in Titik Village, Semen District, Kediri Regency. The method of implementing this service is carried out starting from a survey of waste conditions, socialization of waste processing methods, waste craft training and waste craft marketing training. As a result, the survey found a lack of public awareness of waste, socialization was held to increase knowledge accompanied by training in sorting and making handicrafts according to types of waste, training people to marketing these products. In conclusion, an increasing number of residents are willing to sort waste. PKM partners are able to process various types of waste into economical products and having sale value. The emergence of the enthusiasm of the residents shows that the future of waste craft marketing practices can improve society welfare.